2006
DOI: 10.1289/ehp.7898
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 1-Hydroxypyrene as a Biomarker of PAH Exposure in 3-Year-Old Ukrainian Children

Abstract: Urinary 1-hydroxypyrene (1-OHP) is a biomarker of polycyclic aromatic hydrocarbon (PAH) exposure. We measured urinary 1-OHP in 48 children 3 years of age in Mariupol, Ukraine, who lived near a steel mill and coking facility and compared these with 1-OHP concentrations measured in 42 children of the same age living in the capital city of Kiev, Ukraine. Children living in Mariupol had significantly higher urinary 1-OHP and creatinine-adjusted urinary 1-OHP than did children living in Kiev (adjusted: 0.69 vs. 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
7
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 26 publications
(67 reference statements)
6
49
7
1
Order By: Relevance
“…However, other authors have reported a statistically significant disproportion between genders, higher for women: 0.5 μmol/mol (0.96 μg/g) vs. 0.34μmol/mol (0.66 μg/g) for men, although all the women were non-smokers [24]. This observation was attributed to the amount of time spent in the kitchen for frying and other types of cooking connected with formation of PAHs compounds, and as expected, this difference disappeared among children [25]. The paradox of an inhaled dose of pyrene among nonsmokers being several times lower than the daily urine 1-OHP excretion was reported by Rubino et al, and it was suggested that this may be due to the slow release of pyrene from the soot deposit in the lung alveoli that was trapped in the lungs during life [26].…”
Section: Discussionsupporting
confidence: 52%
“…However, other authors have reported a statistically significant disproportion between genders, higher for women: 0.5 μmol/mol (0.96 μg/g) vs. 0.34μmol/mol (0.66 μg/g) for men, although all the women were non-smokers [24]. This observation was attributed to the amount of time spent in the kitchen for frying and other types of cooking connected with formation of PAHs compounds, and as expected, this difference disappeared among children [25]. The paradox of an inhaled dose of pyrene among nonsmokers being several times lower than the daily urine 1-OHP excretion was reported by Rubino et al, and it was suggested that this may be due to the slow release of pyrene from the soot deposit in the lung alveoli that was trapped in the lungs during life [26].…”
Section: Discussionsupporting
confidence: 52%
“…In our study, the ingestion of smoked paprika at a dose of 2 g per day, clearly over the mean normal value of consumption in general population (0.5g/day), produced a small increase in the urinary excretion of 1-HOP, which was well below the considered risk threshold of 1032 nmol/mol (Hecht et al, 2004;Mucha et al, 2006). These results confirm that smoked paprika from La Vera (Spain) contains small amount of PAH as it has been previously reported (Campillo et al, 2010) and that their chronic ingestion did not affect any clinical parameter so far investigated.…”
Section: Discussionsupporting
confidence: 45%
“…A number of studies have reported the levels of OH-PAHs in occupational groups, including coke oven workers and road pavers (Grimmer et al 1993;Jongeneelen et al 1990; Levin et al 1995), as well as in the general population from various parts of the world (Hansen et al 2005;Mucha et al 2006). In the United States, OH-PAHs are included in the National Health and Nutrition Examination Survey (NHANES) conducted by the Centers for Disease Control and Prevention (CDC), an on-going survey that reports the concentrations of biomarkers in a statistically representative sample of the U.S. population.…”
Section: Introductionmentioning
confidence: 99%